That's pretty complex

Algebra Level 2

If x x is a complex number satisfying x 2 + x + 1 = 0 , x^2+x+1=0, what is the value of x 49 + x 50 + x 51 + x 52 + x 53 ? x^{49}+x^{50}+x^{51}+x^{52}+x^{53}?

1 -1 0 0 1 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Jovan Boh Jo En
May 5, 2018

x 2 + x + 1 = x 3 1 x 1 = 0 x^2+x+1=\frac{x^3-1}{x-1}=0 x 3 + 1 = 0 \implies x^3+1=0 x 3 = 1 x^3=1 Leave the above equation as E q u a t i o n 1 Equation 1 . Next, we have: x 2 + x + 1 = 0 x^2+x+1=0 x 2 + x = 1 x^2+x=-1 Leave the equation as E q u a t i o n 2 Equation 2 . Given the question is: x 49 + x 50 + x 51 + x 52 + x 53 x^{49}+x^{50}+x^{51}+x^{52}+x^{53} = x 49 ( 1 + x + x 2 ) + x 51 ( x + x 2 ) =x^{49}\left(1+x+x^2\right)+x^{51}\left(x+x^2\right) Substitute E q u a t i o n 2 Equation 2 and the given equation in the above equation and we got: x 51 ( 1 ) x^{51}\left(-1\right) Since x 3 = 1 x^3=1 and 51 is a multiple of 3 \text{51 is a multiple of 3} , we can say that x 51 = 1 x^{51}=1 . Thus, 1 ( 1 ) 1\left(-1\right) = -1 =\color{#3D99F6}\text{-1}

How did you derive x 2 + x + 1 = x 3 1 x 1 { x }^{ 2 }+x+1=\frac { { x }^{ 3 }-1 }{ x-1 } ?

Louis Ullman - 3 years ago

Log in to reply

You can try to divide x 3 1 x^3-1 by x 1 x-1 by using long division, you'll get x 2 + x + 1 x^2+x+1 .

Jovan Boh Jo En - 3 years ago

By using long division.

Jovan Boh Jo En - 2 years ago

x 49 + x 50 + x 51 + x 52 + x 53 = x 49 ( 1 + x + x 2 ) + x 51 ( 1 + x + x 2 ) x 51 = x 51 = ( x 3 ) 17 x^{49} + x^{50} + x^{51} + x^{52} + x^{53} = x^{49}(1 + x + x^{2}) + x^{51}(1 + x + x^{2}) - x^{51} = -x^{51} = -(x^{3})^{17} since 1 + x + x 2 = 0 1 + x + x^{2} = 0 .

Next, note that x 2 + x + 1 = 0 x 3 + x 2 + x = 0 x 3 = ( x 2 + x ) = ( 1 ) = 1 x^{2} + x + 1 = 0 \Longrightarrow x^{3} + x^{2} + x = 0 \Longrightarrow x^{3} = -(x^{2} + x) = -(-1) = 1 .

So finally the desired answer is ( x 3 ) 17 = ( 1 ) 17 = 1 -(x^{3})^{17} = -(1)^{17} = \boxed{-1} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...